Selecting e-Purse Smart Card Technology via Fuzzy AHP and ANP - Demirtas, Nurgul; Ozgurler, Senim; Ozgurler, Mesut; Guneri, Ali Fuat (HINDAWI PUBLISHING CORPORATION, 2014)
Developments in the information technologies provide important advantages to consumers and companies. Nowadays, smart card technology starts to use e-purse applications. The aim of this paper is to identify the most important decision criteria to select the best card technology. In this study, at first smart card and multiple selection techniques were explained. Then the best card technology was selected for an e-purse application. The three types of card technologies were examined and the most important criteria were taken into account by the software developer while they develop card software. Fuzzy analytic hierarchy process (FAHP) and analytical network process (ANP) techniques were used to compare smart card technologies.
Keywords: ANALYTIC NETWORK PROCESS; EXTENT ANALYSIS METHOD; GROUP DECISION-MAKING; PROJECT; MACHINE; SYSTEMS; TURKEY; Mathematics